A survey of seed-borne fungi of rice in Malaysia - Wan Nik, Wan Zainun (Malaysian Society of Applied Biology, 1977)
Thirty three fungi were isolated from seed samples of 23 rice varieties collected from 10 locations in West Malaysia and 1 location in Sarawak. The most common pathogen encountered was Tricboconis padwickii. Other pathogens isolated were Drecbslera oryzae, Fusarium moniliforme, Nigrospor oryzae and Pyricularia oryzae